(untitled) (Research, Society and Development, 2023)
The general objective of this study was to critically analyze the category of work and its relationship with the constitution of the social being in an onto-historical process, with the specific objectives being: a) to investigate the category of work and its historicity; b) investigate work as a founding category in the genesis and development of the social being; and c) verify the transformations of the work category and its determinations in the social complexes. In methodological terms, the research was based on the ontological method, from a qualitative approach and a bibliographic investigation. For this purpose, the theoretical propositions of the following authors were fundamentally taken as references: Lessa (2015), Lukács (2013), Marx (2013), among others. The results and discussions pointed out that by transforming nature, the social being alters his consciousness to explore the outside world as he produces new objectivations, generating new causalities and instituting social determinations so that he can modify reality with knowledge of the concrete. In the final considerations, it was emphasized that it is through work that new production relations are developed in which the social being, mainly the working class, goes through an educational process in order to structure a new humanity with techno-scientific qualification.